Gibanje cen lesnih goriv v Sloveniji med letoma 2011 in 2016 - Prislan, Peter (Gozdarski vestnik, 2016)
At the Department for Forest Techniques and Economics of the Slovenian Forestry Institute we have been following the prices of the most frequent forms of wood fuels (firewood, wood chips, briquettes and pellets) twice a year since 2011. In this article we discuss the importance of gathering information and show the price trends of wood fuels between 2011 and 2016 compared with heating oil.
Keywords: drva; lesni peleti; lesni sekanci; briketi; trg; Slovenia; Slovenija